Pengaruh Pajak, Exchange Rate, Intangible Asset, Dan Tunneling Incentive Terhadap Transfer Pricing (Studi Kasus Pada Perusahaan Subsektor Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020- 2024) - Aqil Kurnia Lestari; Nini (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the effect of tax, exchange rate, intangible assets, and tunneling incentive on transfer pricing practices in mining subsector companies listed on the Indonesia Stock Exchange during 2020–2024. The study employs a quantitative approach with a causal research design. The sample was determined using purposive sampling, resulting in 10 companies observed over 5 years, producing 50 firm-year observations. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression with F-test, t-test, and the coefficient of determination (Adjusted R²). The results reveal that, partially, tax, intangible assets, and tunneling incentive do not significantly affect transfer pricing, while the exchange rate has a significant positive effect. The F-test confirms that all four variables jointly influence transfer pricing. The Adjusted R² value of 0.320 indicates that the model explains 32% of the variation in transfer pricing, while the remaining 68% is influenced by other factors outside the model. Theoretically, this research strengthens the literature highlighting the dominance of external factors, particularly exchange rate fluctuations, on transfer pricing practices. Practically, the findings provide implications for the government, companies, investors, and academics to consider exchange rate risk in policy formulation and corporate governance practices.